The effects of melatonin and catalase supplements on the survival of α-Synuclein-expressing saccharomyces cerevisiae cells. - Laura Houghton (The Young Researcher)
Importance: Parkinson’s disease is only one of several conditions classified under Lewy Body Disease, which is characterized by the build-up of the alpha-synuclein protein in neuronal cells. This causes cellular dysfunction and ultimately, cell death. As such, research on this protein is both critical and ongoing. Objective: The purpose of this study was to explore the effects of melatonin and catalase supple- ments on alpha-synuclein-expressing Saccharomyces cerevisiae cells under oxidative stress created by adding H2O2. Design: A mixed-methods research approach and experimental research method were used to investigate changes in cell growth, survival, and morphology. Results: It was determined that the supplements do not have any significant effect on either cell growth or morphology and that melatonin helps to reduce cell death in more severe conditions of oxidative stress. Conclusion: This effect is most likely because of melatonin’s dual ability to both detoxify reactive oxygen species and initiate increased production of antioxidant enzymes like catalase.